2020
DOI: 10.3390/cancers12113323
|View full text |Cite
|
Sign up to set email alerts
|

Mechanisms of Taxane Resistance

Abstract: The taxane family of chemotherapy drugs has been used to treat a variety of mostly epithelial-derived tumors and remain the first-line treatment for some cancers. Despite the improved survival time and reduction of tumor size observed in some patients, many have no response to the drugs or develop resistance over time. Taxane resistance is multi-faceted and involves multiple pathways in proliferation, apoptosis, metabolism, and the transport of foreign substances. In this review, we dive deeper into hypothesiz… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
87
0
3

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 120 publications
(106 citation statements)
references
References 476 publications
(622 reference statements)
1
87
0
3
Order By: Relevance
“…This gene has been implicated in various biological processes, including cancer development and progression (62,63). Recent studies have shown that EPHA3 is down-regulated in chemotherapy-resistant ovarian cancer cells (38) and implicated in regulation of multidrug resistance in small cell lung cancer via the PI3K signaling pathway, which has been frequently linked to taxane resistance (39,64). High expression of circEPHA3.1 and circEPHA3.2 in docetaxel-sensitive breast cancer cells, and their depletion in DRBC cells, indicates that these two circRNAs may be involved in maintaining docetaxel sensitivity in breast cancer cells.…”
Section: Discussionmentioning
confidence: 99%
“…This gene has been implicated in various biological processes, including cancer development and progression (62,63). Recent studies have shown that EPHA3 is down-regulated in chemotherapy-resistant ovarian cancer cells (38) and implicated in regulation of multidrug resistance in small cell lung cancer via the PI3K signaling pathway, which has been frequently linked to taxane resistance (39,64). High expression of circEPHA3.1 and circEPHA3.2 in docetaxel-sensitive breast cancer cells, and their depletion in DRBC cells, indicates that these two circRNAs may be involved in maintaining docetaxel sensitivity in breast cancer cells.…”
Section: Discussionmentioning
confidence: 99%
“…Chemotherapy is the therapeutic option offered to mCPRC patients who have failed other treatment approaches and is mainly based on the use of taxanes (docetaxel, cabazitaxel). Resistance to these drugs is a multifactorial phenomenon in which alterations of microtubule regulatory proteins and tubulin isotopes play a major role [ 122 ].…”
Section: Mirnas Involved In Drug Responsementioning
confidence: 99%
“…Other chemotherapeutic agents widely used are taxanes (e.g., paclitaxel or docetaxel), which stabilise microtubules, disrupt mitosis and cell cycle progression [ 117 ]. However, taxane resistance has been a drawback [ 118 ]. Recent combinatorial approaches between taxanes and small molecules that inhibit Wnt seem to have the potential to combat the resistance by synergising mitotic blockade [ 108 , 118 ].…”
Section: The Tumour Suppressor Apc a Master Rmentioning
confidence: 99%
“…However, taxane resistance has been a drawback [ 118 ]. Recent combinatorial approaches between taxanes and small molecules that inhibit Wnt seem to have the potential to combat the resistance by synergising mitotic blockade [ 108 , 118 ]. One of this Wnt inhibitors is ipafricept (OMP-54F28).…”
Section: The Tumour Suppressor Apc a Master Rmentioning
confidence: 99%